An Ejection Event Captured by Very Long Baseline Interferometry during the Outburst of Swift J1727.8–1613 - Hongmin Cao; Jun Yang; Sándor Frey; Callan M. Wood; James C. A. Miller-Jones; Krisztina É. Gabányi; Giulia Migliori; Marcello Giroletti; Lang Cui; Tao An; Xiaoyu Hong; WeiHua Wang (The Astrophysical Journal Letters)
We observed a newly discovered Galactic black hole X-ray binary Swift J1727.8–1613 with the European VLBI Network (EVN) at 5 GHz. The observation was conducted immediately following a radio quenching event detected by the Karl G. Jansky Very Large Array. The visibility amplitude evolution over time reveals a large-amplitude radio flare and is consistent with an ejection event. The data can be interpreted either as a stationary component (i.e., the radio core) and a moving blob, or as two blobs moving away from the core symmetrically in opposite directions. The initial angular separation speed of the two components was estimated to 30 mas day ^−1 . We respectively fitted a single circular Gaussian model component to each of 14 sliced visibility data sets. For the case of including only European baselines, during the final hour of the EVN observation, the fitted sizes exhibited linear expansion, indicating that the measured sizes were dominated by the angular separation of the two components. The 6 hr EVN observation took place in a rising phase of an even larger 4 day long radio flare, implying that the ejection events were quite frequent and therefore continuous radio monitoring is necessary to correctly estimate the power of the transient jet. Combined with X-ray monitoring data, the radio quenching and subsequent flares/ejections were likely driven by instabilities in the inner hot accretion disk.